Effect of Different Concentrations of Azolla sp. Plant on Protein Concentration in the Gills and Muscles of Grass Carp : Pengaruh Konsentrasi Berbeda Tanaman Azolla sp. terhadap Konsentrasi Protein pada Insang dan Otot Ikan Mas Rumput - Aya Sabah Abdali; Akeil Jameil Mansour (Indonesian Journal on Health Science and Medicine, 2025)
General Background Protein content in fish tissues is closely related to diet composition and nutritional quality in aquaculture systems. Specific Background Azolla sp. is a rapidly growing aquatic plant recognized as a low-cost protein source suitable for herbivorous fish such as grass carp. Knowledge Gap However, limited information is available regarding tissue-specific protein concentration responses, particularly in gills and different muscle regions, following graded dietary Azolla inclusion. Aims This study aimed to evaluate the effects of different Azolla concentrations on protein levels in the gills and muscles of grass carp fingerlings. Results One hundred and twenty fish were fed diets containing 0%, 15%, and 30% Azolla, and protein concentrations were determined using the BCA method. The results showed clear variations in protein concentration across tissues, treatments, and experimental periods, with statistically significant differences observed in gill and muscle regions. Novelty This study provides region-specific evidence of protein distribution in gills and anterior and posterior muscles in response to Azolla-based diets. Implications The findings support the potential use of Azolla as a dietary component in grass carp feeding strategies while highlighting its physiological relevance at the tissue level. Keywords: Azolla Sp., Grass Carp, Gill Protein, Muscle Protein, Plant-Based Feed Key Findings Highlights: Protein concentrations varied significantly among gills and muscle regions across dietary treatments. Distinct responses were observed between anterior and posterior muscle tissues. Graded Azolla inclusion demonstrated tissue-specific nutritional responses.